The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/1040638713493627
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of brain lesions in goats submitted to three veterinary diagnostic laboratories

Abstract: Abstract.A retrospective study of brain lesions in goats was conducted to identify the range of lesions and diseases recognized and to make recommendations regarding the best tissues to examine and tests to conduct in order to maximize the likelihood of making a definitive diagnosis in goats that may have had clinical signs referable to the brain. One hundred thirtynine goats with a brain lesion were identified. The most common lesion, in 52.5% of the goats, was suppurative inflammation. Approximately two-thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
20
0
4
Order By: Relevance
“…In North America, 41.5% of the neurological diseases of sheep are caused by bacteria (Rimoldi et al 2016), similar to the observed in the present study, where these were mainly composed by L. monocytogenes meningoencephalitis, followed by spinal cord abscesses. L. monocytogenes meningoencephalitis in sheep and goats is the main neurological disease caused by bacteria (Oevermann et al 2010, Allen et al 2013, Câmara et al 2014). According to Allen et al (2013), two thirds of the SIND diagnosed in goats from the USA were composed of L. monocytogenes meningoencephalitis, which is similar to the findings of the present study in which 71.42% of the goats were affected by this condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In North America, 41.5% of the neurological diseases of sheep are caused by bacteria (Rimoldi et al 2016), similar to the observed in the present study, where these were mainly composed by L. monocytogenes meningoencephalitis, followed by spinal cord abscesses. L. monocytogenes meningoencephalitis in sheep and goats is the main neurological disease caused by bacteria (Oevermann et al 2010, Allen et al 2013, Câmara et al 2014). According to Allen et al (2013), two thirds of the SIND diagnosed in goats from the USA were composed of L. monocytogenes meningoencephalitis, which is similar to the findings of the present study in which 71.42% of the goats were affected by this condition.…”
Section: Discussionmentioning
confidence: 99%
“…L. monocytogenes meningoencephalitis in sheep and goats is the main neurological disease caused by bacteria (Oevermann et al 2010, Allen et al 2013, Câmara et al 2014). According to Allen et al (2013), two thirds of the SIND diagnosed in goats from the USA were composed of L. monocytogenes meningoencephalitis, which is similar to the findings of the present study in which 71.42% of the goats were affected by this condition. Brugére-Picoux (2008) has described previously that sporadic or outbreaks of the disease are related to the consumption of poorly fermented silage (pH>5.5), which is an important predisposing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of 27 goats with spinal cord lesions, 13/27 (48%) of the goats were diagnosed with degenerative myelopathy. 1 The researchers attributed that 8 of the 13 goats to have lesions suggestive of copper deficiency; and in the remaining 5, 2 had vertebral malformations, and, in the other 3, no underlying cause for the degenerative myelopathy was found. The study did not include the histological examination of the liver so it was not possible to rule out hepatic vasculopathy as a cause of degenerative myelopathy.…”
mentioning
confidence: 99%
“…13,18 Spongy degeneration of the CNS due to hepatocerebral disease and/or hyperammonemia, characterized by diffuse or focal vacuolation, particularly of the white matter, has been reported in a number of young domestic animal species, including sheep, cattle, pigs, and goats. 2,12,29 In this study, serum bile acids were measured in 2 goats and these were elevated. Bile acids have been reported to be elevated in cases of severe liver disease 28 and in juvenile goats with a hepatic portosystemic shunt.…”
mentioning
confidence: 99%